Ngeuyeuk Seureuh Tradition in Sundanese Wedding: Conflict between Custom and Islam Law - Faisal, Muhamad; Makinuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aimed to analyze the process of Ngeuyeuk Seureuh tradition in Sundanese wedding custom and explain the relationship between Ngeuyeuk Seureuh culture and Islam law. This field work built on the study on custom and Islam law in the context of Ngeuyeuk Seureuh tradition in Sundanese custom wedding. Methods of collecting data used were interview and library study. Techniques of analyzing data used were inductive and descriptive data analysis methods. The result of research showed that sundanese wedding custom is the expression of contact between custom and Islam law. Both of them are complementary in each of wedding procession stages, from neundeun omongan, narosan (proposing), seserahan, ngecangkeun aisan, ngaras, siraman, ngerik, to ngeuyeuk seureuh. This study indicated that wedding process related to Islam law in Ngeuyeuk Seureuh tradition is a customary sustainability preserved by Sundanese people from one generation to the next. The wedding organization in Sunda proves that Islam sharia strengthens custom, and vice versa.